THE MOTHERHOOD INSTINCTS OF MALEFICENT AGAINST HER EX-BOYFRIEND’S CHILD IN THE MOVIE “MALEFICENT 1 & 2” - Audina, Chivani Nadia; Mahmud, Murni (Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This research discusses Maleficent's motherhood instinct towards her former lover's child in the movie